Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1109/access.2019.2896342
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Frequency Components Entropy as Novel Heart Rate Variability Indices in Congestive Heart Failure Assessment

Abstract: In this paper, novel heart rate variability (HRV) indices were extracted for the autonomic nervous system (ANS) activity assessment in congestive heart failure (CHF). It has been reported that CHF is a chronic cardiovascular syndrome along with ANS dysfunction, and HRV is a useful tool for ANS assessment. The multi-frequency components Entropy (MFC-En), which is obtained by the Hilbert-Huang transform and the entropy algorithm, was proposed as novel HRV indices for analyzing ANS with CHF. This paper included 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…Therefore, EEMDbased entropy HRV signals analysis provides a new way of assessing the complexity of the rhythm variation of ANS so as to unearth significant clinical information related to diseases. Li et al (2019) proposed a novel descriptor, namely sliding trend fuzzy approximate entropy (SITr-fApEn), based on the empirical mode decomposition (EMD) method for analyzing ANS with obstructive sleep apnea (Li et al, 2019), and Pan et al (2019) introduced a multi-frequency components entropy (MFC-En) based on EMD for CHF classification. MFC-En was verified to be a useful tool for CHF measurement by evaluating the irregularity of rhythm variations of the ANS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, EEMDbased entropy HRV signals analysis provides a new way of assessing the complexity of the rhythm variation of ANS so as to unearth significant clinical information related to diseases. Li et al (2019) proposed a novel descriptor, namely sliding trend fuzzy approximate entropy (SITr-fApEn), based on the empirical mode decomposition (EMD) method for analyzing ANS with obstructive sleep apnea (Li et al, 2019), and Pan et al (2019) introduced a multi-frequency components entropy (MFC-En) based on EMD for CHF classification. MFC-En was verified to be a useful tool for CHF measurement by evaluating the irregularity of rhythm variations of the ANS.…”
Section: Discussionmentioning
confidence: 99%
“…The IMF components are able to represent the energy in specific frequency bands when the central frequency lies within the band limits and the standard deviations are less than twenty percent outside the boundary [ 41 ]. By the Hilbert transform (HT), instantaneous attributes of different time series were calculated [ 25 , 42 ]. The instantaneous frequency is no longer affected by the unnecessary fluctuation caused by the asymmetric waveform thanks to the modified requirements, which makes EMD more suitable for nonstationary signals [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The instantaneous frequency is no longer affected by the unnecessary fluctuation caused by the asymmetric waveform thanks to the modified requirements, which makes EMD more suitable for nonstationary signals [ 37 ]. Furthermore, Pan et al extracted instantaneous frequency of IMFs and demonstrated their correspondence with four physiological subsystems through HT [ 25 ]. The results explained why IMFs were meaningful and could stand for the energy in specific frequency bands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pan et al [60] (see Table 3) Multi-Frequency Components Entropy (or LF/HF) 63.6% to 79.5% (or 86.4%)…”
Section: Referencementioning
confidence: 99%